If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = x + -3y Solving -2 = x + -3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2 + -1x = x + -1x + -3y Combine like terms: x + -1x = 0 -2 + -1x = 0 + -3y -2 + -1x = -3y Add '2' to each side of the equation. -2 + 2 + -1x = 2 + -3y Combine like terms: -2 + 2 = 0 0 + -1x = 2 + -3y -1x = 2 + -3y Divide each side by '-1'. x = -2 + 3y Simplifying x = -2 + 3y
| -14x^2=49 | | p+7774=5p+3p-80 | | 180=90+3x+1+2x+4 | | 2a+a^2=24 | | 8n-20=15+n | | 8x-7(x+3)=1 | | 0.9x=1+x | | Y-5=-3(x+6) | | 9x^2-9y^2-20x-20y+50=0 | | 2x^2-1600=0 | | -2j+2(3j-12)=12j | | 8h+4(-4h+8)=8 | | X^5+3=2 | | -8.93+7.8u=6.91+0.9u+7.7u | | (x*1.5*5)+(x*40)=1000 | | 544=16(w-966) | | 32=-2(8p+8) | | (x*1.5*5)+(x*40)=950 | | -11(z-952)=-209 | | -4.32+16.1m=11.3m | | (x*1.5*5)+(x*40)=900 | | -1.93-8.3r+8.4r=-16.7r-13.69 | | (x*1.5*5)+(x*40)=850 | | 21w--38=983 | | 7x-7(4x+8)=112 | | -7(3x-8)=-21x-56 | | (x*1.5*5)+(x*40)=800 | | 3x=(6X^2-4x+9) | | 5x+20x-50=0 | | 10.6v+6.94=11.2v+15.28 | | (x*1.5*5)+(x*40)=750 | | 2y+6y+5= |